Limosilactobacillus mucosae FZJTZ26M3 prevents NAFLD in mice through modulation of lipid metabolism and gut microbiota dysbiosis - Danting Dang; Bowen Li; Mengfan Ding; R. Paul Ross; Catherine Stanton; Jianxin Zhao; Bo Yang; Wei Chen (Food Science and Human Wellness)
Lactobacillus are considered promising therapeutic methods for nonalcoholic fatty liver disease (NAFLD). The effects of two strains of Limosilactobacillus mucosae on NAFLD were investigated in this study. Four-week-old male C57BL/6J mice were divided into 4 groups (n = 8 per group, Control, Model, FZJTZ26M3, FGSYC17L3). L. mucosae FZJTZ26M3 reduced the mice’s body weight, liver weight, and adipose tissue weight after 12 weeks of therapy. According to serum analysis, total cholesterol, triacylglycerol, and low-density lipoprotein cholesterol significantly decreased after L. mucosae FZJTZ26M3 intervention. Liver pathology showed that L. mucosae FZJTZ26M3 was effective to ameliorate lipid deposition in NAFLD mice. Additionally, the expression of the gene related to lipid metabolism in the liver and adipose tissue was analyzed, and the results indicated that L. mucosae FZJTZ26M3 could alleviate NAFLD by regulating lipid metabolism. Furthermore, the results of 16S rRNA gene sequencing revealed a drop in the relative abundance of Ruminococcaceae, which is linked to inflammation, but the relative abundance of a potential probiotic Akkermansia significantly increased after L. mucosae FZJTZ26M3 intervention. Generally, L. mucosae FZJTZ26M3 could be a candidate to prevent NAFLD.